Europa, siglo XX: filosofías de la resistencia - Reyes, Román (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
From the School of Frankfurt (1937) and the Collège de Sociologie (1937-1939) to Michel Foucault (1970) and Pièrre Bourdieu (1982). Traverse readings of manifestos and tendencies that they have gone generating.